Patterning of light-emitting conjugated polymer nanofibres - Di Benedetto, Francesca; Camposeo, Andrea; Pagliara, Stefano; Mele, Elisa; Persano, Luana; Stabile, Ripalta; Cingolani, Roberto; Pisignano, Dario (Nature nanotechnology, 2008)
Organic materials have revolutionized optoelectronics by their processability, flexibility and low cost, with application to light-emitting devices for full-colour screens 1 , solar cells 2 and lasers 3 , 4 . Some low-dimensional organic semiconductor structures exhibit properties resembling those of inorganics, such as polarized emission 5 and enhanced electroluminescence 6 . One-dimensional metallic, III–V and II–VI nanostructures have also been the subject of intense investigation 7 , 8 as building blocks for nanoelectronics and photonics. Given that one-dimensional polymer nanostructures, such as polymer nanofibres, are compatible with sub-micrometre patterning capability 9 and electromagnetic confinement within subwavelength volumes 8 , they can offer the benefits of organic light sources to nanoscale optics. Here we report on the optical properties of fully conjugated, electrospun polymer nanofibres. We assess their waveguiding performance and emission tuneability in the whole visible range. We demonstrate the enhancement of the fibre forward emission through imprinting periodic nanostructures using room-temperature nanoimprint lithography, and investigate the angular dispersion of differently polarized emitted light. Conjugated polymer fibres offer many advantages over other photonic materials, such as tunable properties and easy processability, making them attractive for optoelectronic applications. The waveguiding performance and emission tunability of fully conjugated, electrospun polymer nanofibres have been assessed and their forward emission shown to improve after periodic structures are imprinted using nanoimprint lithography.